TRANSLANGUAGING AS A PRACTICAL PEDAGOGY BASED ON EDUCATORS’ PERSPECTIVE - Akhmad Hairul Umam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
As new approach of language teaching, translanguaging has become a popular topic and widely debated in applied linguistic for the last few years. This study explored educators’ perspective about the use of translangaging as practical pedagogy in EFL classroom in relation to their position that play a significant role in shifting educational practices. The research data was taken in the form of quantitative and qualitative using questionnaires and interview with participants by involving 15 English educators of Higher Education in Jakarta. The findings revealed positive outlooks on the use translanguaging as pedagogical practices in EFL that gave them opportunities rather as weaknesses like lack of proficiency. In addition, the educators also expressed various perceptions about language as separated system, language mixing, and language as single system that support each other.